Energy harvesting using permanent magnet for power generation - Ramly, Rosmalini; Ahmad, Anita; Leow, Pei Ling; Ishak, Mohd Hafis Izran; Mohamed Ali, Mohamed Sultan (Penerbit UTHM, 2017)
The awareness to be energy efficient in Malaysia is growing in all sectors as well as residential, buildings, industries and transportation. The environment issues which contributes to global warming and climate change through inefficient use of energy not only reflects responsibility to the nation but yield the obligation to be energy efficient in order to ensure optimum cost of operating energy consumption. The Malaysia Government with assistance from Sustainable Energy Development Authority Malaysia (SEDA Malaysia) in Malaysian National Renewable Energy Policy & Action Plan 2010 is forced to identify other alternative energy source with the emphasis on Renewable Energy (RE) in enhancing the utilization of indigenous renewable energy resources to contribute towards national electricity supply security and sustainable socio-economic development.